Community-Based Health Education on Menopausal Transition: A Community Service Program at Mekarjaya Posbindu, Bandung - Maya Sukmayati; Cindy Sonia; Gina Nurjihan; Lupita Dewi (Jurnal Sentra Pengabdian, 2025)
In Indonesia, health education about menopause is rarely integrated into primary care services, and awareness among women remains low. Many women do not recognize early menopausal symptoms or how to manage them effectively. Socioeconomic barriers and low educational attainment further limit access to accurate health information. This situation highlights the need for accessible, community-based education programs. It also underscores the urgency of empowering women with accurate information and culturally sensitive support systems to help them navigate menopausal health more effectively. Currently, many women continue to rely on informal sources or endure symptoms without adequate guidance, making health education and accessible screening even more critical. Surveys indicate that 70% of women undergoing the menopausal transition in Indonesia experience symptoms and discomfort caused by hormonal changes. This community service program focused on delivering health education and promotion to help women become more prepared and confident during the menopausal transition. The intervention was conducted through a structured health education session and screening service for 32 women aged 40–55 at the Posbindu in RW 05, Mekarjaya Village, Bandung. A structured questionnaire was used to assess participants' knowledge before and after the intervention. The results revealed a significant improvement in knowledge; initially, 15 respondents (46.9%) demonstrated poor knowledge, which improved substantially following the education session. In conclusion, direct health education had a positive impact on women's knowledge about the menopausal transition. Sustainable collaboration between educational institutions and local health centers is recommended for future programs